An integrated three-dimensional electrochemical system for efficient treatment of coking wastewater rich in ammonia nitrogen. (May 2020) - Wu, Zhenyu; Zhu, Weiping; Liu, Yang; Peng, Pin; Li, Xiuyan; Zhou, Xiaoqi; Xu, Juan
Abstract: Coking wastewater is highly toxic and refractory industrial wastewater, and is thus extremely challenging to treat. Currently, most treatment technologies focus on degrading carbonaceous pollutants, while insufficient attention is placed on ammonium nitrogen (NH4 + -N), the most important nitrogenous contaminant in coking wastewater and with a high biological toxicity. In the current study, we developed an integrated electrochemical system comprising two three-dimensional electrochemical reactors (3DERs), two three-dimensional biofilm electrode reactors (3DBERs) and one three-dimensional biofilm electrode reactor for denitrification (3DBER-De) to treat coking wastewater rich in NH4 + -N. Our integrated system is able to remove 70.7% of total nitrogen (TN) at the low energy consumption of 1.29 kWh m −3, and can reduce COD by 55.8%. The 3DERs primarily degrade NH4 + -N, nitrate nitrogen (NO3 − -N), and COD by electrochemical redox reactions, while the 3DBERs convert residual NH4 + -N to NO3 − -N by fusing biofilm and electricity. Moreover, the 3DBER-De further eliminates NO3 − -N by bio-electrochemical denitrification. The coking wastewater is purified as it flows through the integrated treatment system, with only a few hydrocarbon residuals detected that are able to be readily biodegraded by conventional biological treatments. The proposed 3DERs/3DBERs/3DBER-De system provides a new solution for coking wastewater with high concentrations of NH4 + -N. Graphical abstract: Image 1 Highlights: Ammonia-rich coking wastewater is treated by an integrated electrochemical system. 3DERs are responsible for partial removal of NH4 + -N, NO3 − -N and COD. 3DBERs convert NH4 + -N to NO3 − -N by nitrification. 3DBER-De eliminates NO3 − -N by denitrification. 70.7% of TN and 55.8% of COD are removed at energy consumption of 1.29 kWh/m 3 .